Exploring the Link Between Loneliness and Poverty in Emerging Economies - Elgueta-Rosas, R (ELSEVIER, 2025)
Loneliness is a significant public health issue affecting diverse populations. This study aimed to examine the association between poverty and loneliness in emerging economies, defined by the World Bank as nondeveloped countries. A systematic review was conducted using the Scopus and Web of Science databases to identify studies published from 2020 onward that examined loneliness and poverty-related variables. After applying the exclusion criteria, only 76 articles were included in the analysis, most from China, India, and South Korea, with limited representation from Latin America and Africa. The findings indicate that poverty is a predictor of loneliness. However, the majority of studies examined poverty and loneliness as independent predictors of third outcomes, primarily mental health issues, such as depressive symptoms or reduced well-being. Only a few studies explored the mechanisms underlying these relationships, with limited mediation and moderation analyses. Additionally, the scarcity of longitudinal research limits causal interpretations.